Pengaruh Faktor Sosial, Ekonomi dan Lingkungan Tempat Tinggal Terhadap Pendidikan Anak Nelayan di Kabupaten Tanjung Jabung Timur - Asmaida, Asmaida; Saputra, Ryan Septiandri (Jurnal MeA (Media Agribisnis), 2025)
Fishermen, as a traditional society, are perceived as having socio-economic conditions that are still lagging behind, and their education remains weak. Policies regarding socio-economic conditions related to education, health, economy, infrastructure, and institutions, which aim to develop their human resources that continue to lag, need to be reviewed as an effort to improve living standards and to create a smart, advanced and prosperous society. This study focuses on the influence of income factors, age, fishermen's education, number of family dependents, distance to educational facilities, environmental conditions, and social status on the education of fisher children in East Tanjung Jabung Regency. The sample involved purposive incidental sampling of 70 fishermen as respondents. The analysis method employed a quantitative descriptive approach, with data being analysed using the SPSS program version 21.0. The results of the study showed that the variables of income, fishermen's education, the number of family dependents, the distance from the place of education, and social status had a significant effect on the variables of the education level of fisher children in East Tanjung Jabung Regency. Meanwhile, the variables of the age of fishermen and environmental conditions had no effect on the variables of the education level of fishermen's children.